The effect of rapid weight loss on body composition and circulating markers of creatine metabolism in judokas - Drid, Patrik (Array, 2019)
We evaluated the effects of a 7-day rapid weight loss (RWL) intervention on body composition and biomarkers of creatine metabolism in eight elite judokas during a pre-competition period. RWL induced a significant drop in weight (81.7±10.7 kg at baseline vs. 76.8 ± 10.3 kg at follow-up; p<.001), fat mass (12.6±5.6 kg vs. 9.2±4.0 kg; p=.003) and fat-free mass (69.1±7.3 kg vs. 67.6±7.7 kg; p=.05), accompanied by an increase in serum creatinine levels at follow-up (104.0±10.5 µmol/L vs. 114.9±10.2 µmol/L; p=.009). An acute restriction of food and fluid intake appears to negatively affect fat-free mass and indices of kidney function in judokas.